Enseñar y evaluar textos narrativos. Algo más que puro cuento - Saúl Gil, John (Enunciación, 2010)
This article presents the results of a research on the didactics of narrative texts, particularly on the evaluation of this type of texts in the writing compositions of a group of students registered in first semester of Modern Languages in Universidad del Valle. This study makes an approach to the topic of the didactics of narrative texts and inquires on the formative character of evaluation and on what could be evaluated in aspecific time of teaching. Then, it suggests poetical, textual and intertextual categories for an approachthat value the writing compositions of students. Finally, some preliminary conclusions are proposed.